Smooth muscle CaMKII [delta] promotes allergen-induced airway hyperresponsiveness and inflammation - Spinelli, Amy; Liu, Yongfeng; Sun, Li-Yan; González-Cobos, José C.; Backs, Johannes; Trebak, Mohamed; Singer, Harold A. (Pflügers Archiv, 2015)
Airway smooth muscle (ASM) is a key target cell in allergen-induced asthma known to contribute to airway hyperresponsiveness (AHR) and chronic airway remodeling. Changes in ASM calcium homeostasis have been shown to contribute to AHR although the mechanisms and Ca2+ signal effectors are incompletely understood. In the present study, we tested the function of ASM multifunctional protein kinase Ca2+/calmodulin-dependent kinase II (CaMKII) isoforms CaMKIIδ and CaMKIIγ in allergen-induced AHR and airway remodeling in vivo. Using a murine model of atopic asthma, we demonstrate that CaMKIIδ protein is upregulated in ASM derived from ovalbumin (OVA)-treated animals compared to controls. A genetic approach to conditionally knock out smooth muscle CaMKIIδ and CaMKIIγ in separate Cre-loxp systems was validated, and using this loss-of-function approach, the function of these CaMKII isoforms was tested in ovalbumin (OVA)-induced airway remodeling and AHR. OVA treatment in control mice had no effect on ASM remodeling in this model of AHR, and CaMKIIδ knockouts had no independent effects on ASM content. However, at 1 day post-final OVA challenge, OVA-induced AHR was eliminated in the CaMKIIδ knockouts. OVA-induced peribronchial inflammation and bronchoalveolar lavage fluid (BALF) levels of the Th2 cytokine IL-13 were significantly decreased in the CaMKIIδ knockouts. Unexpectedly, we found increased peribronchial eosinophils in the smooth muscle CaMKIIδ knockouts compared to control animals at 1 day post-final challenge, suggesting that lack of ASM CaMKIIδ delays the progression of AHR rather than inhibiting it. Indeed, when AHR was determined at 7 days post-final OVA challenge, CaMKIIδ knockouts showed robust AHR while AHR was fully resolved in OVA-challenged control mice. These in vivo studies demonstrate a role for smooth muscle CaMKIIδ in promoting airway inflammation and AHR and suggest a complex signaling role for CaMKIIδ in regulating ASM function. These studies confirm the diverse roles of ASM cells as immune effectors that control AHR and call for further studies into CaMKIIδ-mediated signaling in ASM cells during disease.
Im Titel ist delta als griechischer Buchstabe dargestellt
Gesehen am 19.06.2020